Short Review on Types of Heat Shock Proteins and Their Fundamental Characters for Body Maintenance Together With Role in Cancer - Muneeb, Muhammad; Ali, Moazam; Sarfaraz, Tahir; Ali, Wajid; Bhutta, Zeeshan Ahmad (Himalayan Journal of Science and Technology, 2020)
Body of living thing is a complex machine that works on multifunctional processes and needs maintenance. Heat shock protein is a specific type of protein that cares about many normal functions of the body. These proteins have many dynamic occupations to shield the body from various diseases and also a key role in the coiling and uncoiling of proteins, prevent from apoptosis and transportation of proteins. Along with these all properties, the foremost function of these proteins is prevention from cancer and a significant role in cancer diagnosis. Commonly heat shock protein known as chaperones and a wide range of their types have been discovered with their functions as well. Recently many scientists are working on additional investigation of heat shock proteins. This review concludes some basic types of heat shock proteins and their elegant purposes and also providing an open eye for new scientist about a further investigation of heat shock protein.